Administration of Educational Institution Administrators According to Buddhist Principles - Boonwas, Nanthaphorn; Uttaro (Makdee), Phramaha Udorn (Mahachula Academic Journal, 2023)
The objective of this journal was to study the administration of the educational institution administrators according to the Buddhist principles. The school administration was the key role of the administrators that specified the styles, methods and procedures in working systematically with the Buddhist principles as the leader and the practice of the organization. The administrators must hold on the Dutiyapapanika-dhamma (three qualities of a successful business): (1) Cakkhuma (shrewd), (2) Vidhuro (capable of administering business) and (3) Nissayasampanno (having a good credit rating). The personnel administration should apply the Sikkhattaya (the Threefold Training). Moreover, the administration in the schools should apply the 3 P: (1) Pariyatti (study of the Scripture), (2) Patipatti (the practice) and (3) Pativedha (realization), and the Sappurisadhamma (the seven qualities of a good man. The good administrators should select the ways for administration suitable and efficient for the goals. Moreover, the administration should apply the science and art.